Dukungan Sosial Pada Pasien Skizofrenia - Hidayat, Asep Wahyudin; Riyantina, Ade Sity; Hertini, Reni; Nurjanah, Nurjanah; Rofiah, Rofi; Muflihah, Muflihah; Lestari, Suci Dwi (Yayasan Inspirasi El Burhani, 2024)
Introduction: Schizophrenia is a psychotic disorder characterized by disturbed thoughts, emotions and behavior. Schizophrenia occurs due to chemical abnormalities in the brain so that nerve impulses and systemic functions are disrupted. This makes sufferers unable to process information from and to the five senses so that inappropriate projections appear Objective: The samples that were used as research subjects were 96 respondents Method: This type of research is a type of quantitative analytic research using a cross sectional approach. In this study data collection for the independent variable and the dependent variable was carried out simultaneously based on the status of the situation at that time (data collection), namely the relationship between stress levels and blood pressure in the elderly. Result: this program was successful in providing knowledge about social support for schizophrenia patients. Conclusion: In conclusion, this program was successful in providing knowledge about social support for schizophrenia patients.